EVIDENCE FOR HYDROUS HIGH-MGO MELTS IN THE PRECAMBRIAN - Stone W.E.; Larson M.S.; Lesher Michael C.; Deloule E. (My University, 1997)
Prevailing petrogenetic models for Precambrian high-MgO melts such as komatiites invoke crystallization from nearly anhydrous melts (≪0.5% H2O) generated by partial melting of mantle peridotite at temperatures of (≤ 1900 °C and pressures of (18 GPa. However, ultramafic cumulate and gabbro zones of komatiitic and other high-MgO units in Precambrian greenstone belts contain vesicles and minor to major amounts (≤ 25%) of igneous amphibole. The textures (oikocrysts, rims on intercumulate pyroxene, and mineral inclusions within orthocumulate olivine) and the water-rich compositions (1.00% 2.50% H2O) of igneous amphiboles from the Archean Abitibi belt indicate crystallization in situ from significantly hydrous melts while the melt fraction was still as high as 40% 50%. Comparisons to experimental phase equilibria suggest that the residual melts from which the amphiboles crystallized contained 3% 4% H2O, and adjustments for fractional crystallization suggest that the initial melts may have contained as much as 2% H2O. H2O contents of this magnitude would require substantial revision of the nearly anhydrous models for Precambrian high-MgO melts, possibly permitting generation at lower temperatures and pressures, lowering their densities and viscosities, increasing their eruptibility, and enhancing the formation of spinifex textures.
Keywords: Precambrian; Precambrian; Докембрий